Virtual tourist satisfaction in the post-pandemic reality: economic-financial benefit - Fernández Calvo, Víctor; Rühl, Alexander; Kubus, Renata (Mercados y Negocios, 2022)
The work aims to analyse how virtual tourism viability is achieved in face of post-pandemic reality stemming from economic and financial flows for companies in the sector. The analysis is based on surveys from organisations such as MCI Spain and EventoPlus as well as information obtained from ten professional congresses on health, research as well as corporate topics. Five of these are face-to-face (pre-pandemic), four are virtual and one is hybrid (post-pandemic). The results show that virtual events viability is mainly achieved by sustainability, security, audio-visual elements, and types of event formats. The main conclusion is that the post-pandemic reality demands from congress tourism the creation of new, smart and sustainable ideas to improve the overall satisfaction of value chain participants.